Preliminary analysis and design of 4kW@4.5K helium refrigerator for CFETR toroidal field magnet test facility. Issue 1 (1st May 2022) - Lu, X F; Zhang, Q Y; Zhou, Z W; Chen, A Y; Zhu, P; Li, S S
Abstract: China Fusion Engineering Test Reactor (CFETR) is the next magnetic confinement fusion device to demonstrate fusion energy. To test the cryogenic performance of CFETR Toroidal Field (TF) superconducting magnet, a large-scale helium cryogenic system was under construction to provide Supercritical Helium (SHe), supported by Comprehensive Research Facility for Fusion Technology (CRAFT). In this paper, heat loads of TF magnet and the dedicated distribution system were analysed to define the scale. Process flow of the helium refrigerator has been designed considering the various operation phases. Preliminary thermodynamic cycle of the helium refrigerator have been calculated with the capacity of 4kW@4.5K+20g/s@50K. This 4kW@4.5K helium refrigerator was not only a test facility for CFETR superconducting magnets, but also a prototype of CFETR helium refrigerator.